KEKERASAN VERBAL DALAM VIDEO MONOLOG AKUN INSTAGRAM @ismaillishtkroo - Camelia Fitri Rahmawati; Agustina Agustina (Jurnal Bahasa dan Sastra, 2019)
This research was conducted to describe (1) the types of speech acts, (2) the speech act functions; (3) the types of verbal violence in the monologue video account @ismaillishtkroo. This type of research is a qualitative study using descriptive method. The object of this study is a speech containing verbal violence in monologue and comet video on the Instagram account @ismaillishtkroo. The data taken was analyzed with the following steps: (1) transcribing spoken language in the video into written language, (2) identifying data in accordance with the aspects studied, (3) classifying research data by creating tables based on aspects that are researched, (4) interpreting data, (5) inferring data based on research results. In this study, found the following 3 things. First, the types of speech acts that found are expressive, directive, assertive and commissive. Second, the speech act function found is a contradictory and competitive function. Third, the types of verbal violence found are curse, ridicule, accusations, intimidation, insults, coercion, threats, harassment, curses, and rebuke.